Design and implementation of two-phase permanent magnet synchronous motor fed by a matrix converter - Aydogmus, Omur; Deniz, Erkan (Inst Engineering Technology-Iet, 2017)
A direct matrix converter structure and a two-phase permanent magnet synchronous motor (PMSM) are designed to increase the system efficiency in low-power motor drive applications. The drive system with two-phase PMSM has been proposed instead of the single-phase squirrel cage induction motor, which has low efficiency. A constant AC single-phase power supply can be directly converted to frequency and amplitude-adjustable two-phase power supply by the proposed converter structure. However, the proposed converter cannot generate the sufficient voltage level for a standard commercial motor. For this reason, a new two-phase PMSM is designed to adapt the converter output voltage amplitude with the motor-rated voltage by using Infolytica/MotorSolve software. A novel switching algorithm has been developed and analysed to show output voltage-current waveforms of the converter with their harmonic spectrum. In addition, the converter is designed compactly to be mounted to the terminal box of the designed motor. Experimental results have been obtained for speed control of the motor by using vector control at different reference speeds.
Keywords: Induction-Motor; Drive; Modulation; Capacitor